(untitled) (Global Journal of Human-Social Science, 2022)
This article argues that preaching may help people in northern Nigeria to acquire vision of a better life through faith in God because the Word of God have the capacity to give people in a situation of poverty and unemployment both vision and inspiration that may empower them to enhance their circumstances and bring about liberation from their situation of poverty. Stated differently, preaching may help people who feel they are hopeless and useless to see themselves as capable and having worth and value because the word of God have the power to inspire, motivate and drive people in the situation of poverty to open up new vistas, a vision, and hope to improve their situation. As such the article consider economic preaching as preaching that stimulates people to trust in God’s ability, preaching that create awareness, preaching that motivate the practice of koinonia, and preaching that stir up hope in God.